Impact of business regulations on foreign direct investment inflows and economic growth in East African countries - Getaye Gizaw; Habtamu Kefelegn; Bewuketu Minwuye; Gizachew Mengesha; Daregot Berihun (Cogent Economics & Finance, 2023)
Continuous improvement of the business environment is important for countries seeking to benefit from increased trade and investment through regional integration. Creating an enabling environment for businesses to thrive and expand has become a new concept in international development organizations, and a good business climate allows good ideas to take root, which leads to the creation of jobs and better lives for host countries. The main objective of this study was to investigate the impact of business regulations on FDI inflow and economic growth in East Africa region using data collected from the World Bank spanning from 2010-2019. The study finds that dealing with construction, enforcing contracts, getting credit, getting electricity, paying tax and protecting minority investors have a significant impact on FDI inflow in the region. While enforcing contracts, getting credit, protecting minority investors, resolving insolvency, starting a business and trade across borders have a significant impact on economic growth in the region. Moreover, each additional reform during 2010-2019 is associated, on average, with a 3.09% increase in FDI inflows and 2.24% increase in GDP in East African countries. The findings of this study will help policy makers in the region to establish a strong legal framework of business regulations to attract FDI inflow into their economies, to adjust their ease of doing business procedures to attract FDI to their economies and to promote regional economic growth. This will also assist investors in monitoring these key indicators to facilitate investment decisions in foreign countries.
Keywords: 330; Business regulation; economic growth; effect; foreign direct investment